Przestrzenne aspekty współpracy gospodarczej na pograniczu polsko-niemieckim na przykładzie Dolnego Śląska i Saksonii - Adamczuk, Franciszek (Global aspects of the economic cooperation on the Polish-German border on the example of Lower Silesia and Saxony Regions, 2006)
The article is concerns global aspects of regional cooperation in Europe at the level NUTS 2, namely the Dolnośląskie voivodship, which is informally called Lower Silesia, and the German bordering region, shorly called Saxony. The author discusses all important documents connected with global development in both regions. He pays attention to documents prepared separately by these regions’ governments as well as to those prepared together, especially to the results of the ongoing discussion about development strategy of Lower Silesia until 2020 (presently in preparation). Conclusions and the evaluation of the analyzed problem, which may have some significance in both research and practice, are presented in the last part of the paper
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 191-201